Carbon nanotubes enhancement of fiber Bragg grating surface plasmon resonance sensor - Thirunavakkarasu, Punithavathi; Khan, Abdul Ali; Shabaneh, Arafat; Saidin, Norazlina; Sulaiman, Muhammad Syahnizam; Muhammad Noor, Ahmad Shukri (IEEE, 2023)
In this research, a telecommunication standard fiber Bragg grating is sputtered with a 45 nm gold film to obtain surface plasmon resonance. Carbon nanotubes are deposited over the gold layer for sensitivity enhancement due to its unique chemical and optical properties. The developed sensor is interrogated with a broad-spectrum light source and spectrophotometer setup in the visible region and the sensing performance is analyzed. The sensor showed high sensitivity of 526 nm/RIU which was more than 4 time higher than a sensor without the carbon nanotubes enhancement. This shows great promise in the application of CNTs and possibly other sensitive nanomaterials as sensing enhancements of future sensing using optical fibers.